THE EFFECT OF IRON AND VITAMIN C SUPPLEMENTS ON HEMOGLOBIN LEVELS OF PREGNANT WOMEN WITH ANEMIA: SYSTEMATIC LITERATURE REVIEW - Murtiningsih Murtiningsih; Lita Lestari; Hemi Fitriani (Journal of Maternity Care and Reproductive Health, 2021)
Women experience hematocrit levels change during pregnancy. It can be occurs by blood hemodelusion than women sucretible to have anemia. Vitamin C is one of solution that can be increase iron absorption. The aim of this research is to identify how the effect of giving iron and vitamin C supplement on hemoglobin levels in pregnant women with anemia. Type the study is Systematic Literature Review Approach (SLR). Data collecting based on PRISMA flow chart diagram that use 4 database i.e. DOAJ, Google Search Advance, NCBI (PubMed) and Garuda with keyword “zat besi dan anemia dan hb dan kehamilan” dan kunci “Iron AND anemia AND hemoglobin levels and pregnancy” that find out 543 articles. Only 5 articles that is compatible with eligibility criteria by CASP random control trials checklist. Results: Five articles has been report that giving iron and vitamin C supplement is effective to increase hemoglobin levels on pregnancy than iron supplementation without combining with vitamin C supplement. The increase of Hb levels in intervention group that given iron and vitamin C was greater than control group that given iron without vitamin C. There was a significant effect of giving combination iron and vitamin C supplement on hemoglobin levels in pregnant women. Recommendation: Further research is needed on the administration of iron and vitamin C with more samples, different characteristics, and by cohort.